Comparative study of two tsunamigenic earthquakes in the Solomon Islands: 2015 Mw 7.0 normal‐fault and 2013 Santa Cruz Mw 8.0 megathrust earthquakes. Issue 9 (7th May 2016) - Heidarzadeh, Mohammad; Harada, Tomoya; Satake, Kenji; Ishibe, Takeo; Gusman, Aditya Riadi
Abstract: The July 2015 Mw 7.0 Solomon Islands tsunamigenic earthquake occurred 40 km north of the February 2013 Mw 8.0 Santa Cruz earthquake. The proximity of the two epicenters provided unique opportunities for a comparative study of their source mechanisms and tsunami generation. The 2013 earthquake was an interplate event having a thrust focal mechanism at a depth of 30 km while the 2015 event was a normal‐fault earthquake occurring at a shallow depth of 10 km in the overriding Pacific Plate. A combined use of tsunami and teleseismic data from the 2015 event revealed the north dipping fault plane and a rupture velocity of 3.6 km/s. Stress transfer analysis revealed that the 2015 earthquake occurred in a region with increased Coulomb stress following the 2013 earthquake. Spectral deconvolution, assuming the 2015 tsunami as empirical Green's function, indicated the source periods of the 2013 Santa Cruz tsunami as 10 and 22 min. Key Points: Proximity of 2013 and 2015 events enabled spectral deconvolution of tsunami waveforms to estimate 2013 source periods of 10 and 22 min High rupture velocity of 3.6 km/s on north dipping normal‐fault plane for the 2015 Solomon Islands earthquake Positive stress transfer by the 2013 Santa Cruz earthquake to the 2015 Solomon Islands earthquake